TRAJECTORIES OF SERUM 25(OH)D IN CHILDREN WITH PARALYTIC SYNDROMES WHEN USING VITAMIN D FROM DIFFERENT MANUFACTURERS AND IN DIFFERENT DOSES - О. Ріга; О. Міхайлова (Неонатологія, хірургія та перинатальна медицина, 2023)
The prevalence of vitamin D deficiency and insufficiency varies significantly in different subpopulations of children depending on age and diseases, and recommendations for their correction in children with paralytic syndromes are limited. Aim. Empirical determination of blood 25(OH)D trajectory in children with paralytic syndromes when using vitamin D from different manufacturers and in different doses. Material and methods. The 25(OH)D (ng/ml) of blood serum was analyzed by immune-enzymatic method "Labline-90" (Austria) with the test system "Monobind Inc." (ELISA, USA) in 77 children with paralytic syndromes aged 1-18 years, a repeat study after vitamin D3 supplementation was conducted in 36 children. The rate of increase in 25(OH)D concentration per month was calculated. Methods of descriptive statistics, non-parametric correlation analysis and Kaplan-Meier survival analysis were used with MedCalc Statistical Software (Belgium). This study was approved by the Ethics Committee (protocol No. 5, October 2021), which was conducted with the involvement of minor patients and did not contain measures that could harm their health. The research was carried out within the framework of the Department of Pediatrics of Kharkiv National Medical University "Medical and social aspects of adaptation of children with somatic pathology in modern conditions" (state registration number 0120U102471, 2020). Results. Vitamin D insufficiency was diagnosed in 17% of children with paralytic syndromes, and vitamin D deficiency in 73%, so daily doses of 2000-4000 IU of vitamin D3 from different manufacturers were recommended at the discretion of the parents for 6 months. In reality, children received doses from 500 to 5000 IU randomly, from 2 to 7 months. Doses were stratified as greater than 2000 IU and less than 2000 IU. If the child received a dose of 2000 IU or more, the rate of increase of 25(OH)D in the blood in children was 3.6 ng/ml per month, if the dose was less than 2000 IU - 1.6 ng/ml per month. Conclusions. Children with paralytic syndromes should be screened and monitored for serum 25(OH)D levels. With a serum 25(OH)D level of less than 20 ng/ml, daily administration of vitamin D3 in a dose of at least 2000 IU for at least 6 months allows reaching a 25(OH)D level of 30 ng/ml in most of them. Further large-scale studies are needed to supplement current recommendations for vitamin D3 supplementation in children with paralytic syndromes.